Analisis Sektor-Sektor Unggulan di Provinsi Riau - Tomi Ramadani; Irsyah Putra Sagala; Puti Andiny; Safuridar Safuridar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Riau Province is one of the largest contributors to GRDP in Indonesia with several leading sectors. This study aims to determine the leading sectors or base and non-base sectors in Riau Province. The data used in this study are secondary data obtained from the Riau Province Central Bureau of Statistics (BPS). The data was processed and analysed using the Location Quotient (LQ) analysis method. The results of Location Quotient (LQ) analysis show that there are 3 basic sectors or leading sectors in Riau Province for the 2018-2022 period. It is known that there are 3 basic sectors or leading sectors in Riau Province, the 3 sectors are the Agriculture, Forestry and Fisheries sector, the Mining and Quarrying sector, and the Manufacturing Industry sector with LQ analysis values of 2.15, 2.23, and 1.52, respectively. While the other 14 sectors are non-base sectors. For this reason, the government must better understand what sectors need to be improved and the need for cooperation from many parties so that these leading sectors can be maintained and further developed in the following year.